Educational influence on women’s colour perception: C1 eventrelated component analysis (Bangladesh Journal of Medical Science, 2024)
Objective This study aimed to investigate colour perception in women from different educational groups using an event-related potential (ERP) analysis to examine the influence of education on colour processing among women.Materials and methods Twenty-four age-matched women, from high-, medium-, and low-education groups (n = 8 in each group), were recruited in this study. 128-ERP net was used for the ERP study. All women presented their like or dislike for a particular colour by pressing button ‘1’ or ‘2’, respectively. Nine electrodes were chosen to analyse the amplitudes and latencies of the C1 ERP component.Results and Discussion We found no significant differences in the amplitudes and latencies of the C1 ERP component between groups. A smaller amplitude of the C1 component indicated good perceptual learning, and no significant change indicated spatial or featurebased neutral stimuli. In this study, no significant change in the C1 amplitude was found, and we inferred that education did not influence colour processing, as colour was possibly a featurebased neutral stimulus for women. Conclusion: Education did not influence colour perception in women.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 471-475